Exportación al mercado francés, de palmito producido y procesado en la provincia de Pichincha en envases de vidrio y conserva de vinagre - Egüez Vásquez, María Daniela (2011)
This study aims to conduct a market research study to analyze the main competitors and suppliers, as well as production at a country and province level. According to information we can verify that the increased export of palmito has been maintained in recent years, since its most important strengths such as climate, soil and geographical location, have allowed the production and sales levels to increase towards the French market and thus remain as the world´s leading producer and exporter